Intestinal Epithelial Cell Regulation of Adaptive Immune Dysfunction in Human Type 1 Diabetes - Graves, Christina L.; Li, Jian; LaPato, Melissa; Shapiro, Melanie R.; Glover, Sarah C.; Wallet, Mark A.; Wallet, Shannon M. (Frontiers in Immunology, 2017)
Environmental factors contribute to the initiation, progression, and maintenance of type 1 diabetes (T1D), although a single environmental trigger for disease has not been identified. Studies have documented the contribution of immunity within the gastrointestinal tract (GI) to the expression of autoimmunity at distal sites. Intestinal epithelial cells (IECs) regulate local and systemic immunologic homeostasis through physical and biochemical interactions with innate and adaptive immune populations. We hypothesize that a loss in the tolerance-inducing nature of the GI tract occurs within T1D and is due to altered IECs’ innate immune function. As a first step in addressing this hypothesis, we contrasted the global immune microenvironment within the GI tract of individuals with T1D as well as evaluated the IEC-specific effects on adaptive immune cell phenotypes. The soluble and cellular immune microenvironment within the duodenum, the soluble mediator profile of primary IECs derived from the same duodenal tissues, and the effect of the primary IECs’ soluble mediator profile on T-cell expansion and polarization were evaluated. Higher levels of IL-17C and beta-defensin 2 (BD-2) mRNA in the T1D-duodenum were observed. Higher frequencies of type 1 innate lymphoid cells (ILC1) and CD8+CXCR3+ T-cells (Tc1) were also observed in T1D-duodenal tissues, concomitant with lower frequencies of type 3 ILC (ILC3) and CD8+CCR6+ T-cells (Tc17). Higher levels of proinflammatory mediators (IL-17C and BD-2) in the absence of similar changes in mediators associated with homeostasis (interleukin 10 and thymic stromal lymphopoietin) were also observed in T1D-derived primary IEC cultures. T1D-derived IEC culture supernatants induced more robust CD8+ T-cell proliferation along with enhanced polarization of Tc1 populations, at the expense of Tc17 polarization, as well as the expansion of CXCR3+CCR6+/− Tregs, indicative of a Th1-like and less regulatory phenotype. These data demonstrate a proinflammatory microenvironment of the T1D-duodenum, whereby IECs have the potential to contribute to the expansion and polarization of innate and adaptive immune cells. Although these data do not discern whether these observations are not simply a consequence of T1D, the data indicate that the T1D-GI tract has the capacity to foster a permissive environment under which autoreactive T-cells could be expanded and polarized.